TINJAUAN KOMUNIKASI ISLAM TENTANG DAMPAK JEJARING SOSIAL FACEBOOK (KASUS PADA MAHASISWA STAIN PAREPARE - Ariyanti Aris; Uswatun hasanah; Iskandar Iskandar (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
This study aims to determine the review of communications Islam against the facebook social networking users, knowing ethics STAIN students using the facebook social networking in communications Islam, and to investigate the impact of social networking on communications antrapribadi facebook for students STAIN. In the process the existing data, the authors used qualitative data processing. Qualitative research conducted by using data analysis required inductive approach, the method is performed for analyzing the data based on the data or events that are specific to draw general conclusions. Engineering technique used is sampling purposive